Berbagai Penyebutan Anak dalam Al-Qur’an: Implikasi Maknanya dalam Konteks Qura’anic Parenting - Abdul Mustaqim (Jurnal Lektur Keagamaan, 2015)
This article aims to explain about the variant of the Qur’an terms concerning to the words of children. By using thematic method and semantic approach, the research result shows that there are many terms mentioned in the qur’anic verses about the children, namely: al-walad, al-ibn, al-bint, dzurriyyah, al-ghulam ect. Some experts say that those terms have similar meaning, while in the qur’anic semantic itself, they are not really similar. It isbecause each of the terms tends to show a certain meaning that very important to be considered in the issues of qur’anic parenting.